Forecasting Raw Material Inventory Using Exponential Smoothing and Moving Average Methods - Yasmin Humaira Rahmad (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2024)
The production process is carried out to convert raw materials into finished products. One factor that influences the smooth running of production is the availability of sufficient raw materials. PT X, which produces carton boxes, currently needs help predicting production needs. This research aims to determine the appropriate raw material forecasting method by comparing two methods, namely exponential smoothing and moving average. The moving value used in the moving average method is 2, while the alpha (α) value used in the exponential smoothing method is 0.1. The forecasting results using these two methods were then tested for error levels. The forecast error level test results show that the exponential smoothing forecasting method with a value of α = 0.1 has the lowest error value compared to the moving average method.